Do myeloproliferative neoplasms and multiple myeloma share the same genetic susceptibility loci?. Issue 7 (27th October 2020) - Macauda, Angelica; Giaccherini, Matteo; Sainz, Juan; Gemignani, Federica; Sgherza, Nicola; Sánchez‐Maldonado, José Manuel; Gora‐Tybor, Joanna; Martinez‐Lopez, Joaquin; Carreño‐Tarragona, Gonzalo; Jerez, Andrés; Spadano, Raffaele; Gołos, Aleksandra; et al.
Abstract: Myeloproliferative neoplasms (MPNs) are a group of diseases that cause myeloid hematopoietic cells to overproliferate. Epidemiological and familial studies suggest that genetic factors contribute to the risk of developing MPN, but the genetic susceptibility of MPN is still not well known. Indeed, only few loci are known to have a clear role in the predisposition to this disease. Some studies reported a diagnosis of MPNs and multiple myeloma (MM) in the same patients, but the biological causes are still unclear. We tested the hypothesis that the two diseases share at least partly the same genetic risk loci. In the context of a European multicenter study with 460 cases and 880 controls, we analyzed the effect of the known MM risk loci, individually and in a polygenic risk score (PRS). The most significant result was obtained among patients with chronic myeloid leukemia (CML) for PS0RS1C1‐ rs2285803, which showed to be associated with an increased risk (OR = 3.28, 95% CI 1.79‐6.02, P = .00012, P = .00276 when taking into account multiple testing). Additionally, the PRS showed an association with MPN risk when comparing the last with the first quartile of the PRS (OR = 2.39, 95% CI 1.64‐3.48, P = 5.98 × 10 −6 ). In conclusion, our results suggest a potential common genetic background between MPN and MM, which needs to be further investigated. Abstract : What's new? Myeloproliferative neoplasms (MPN) are a rare and heterogeneous group of diseases, and the genetic susceptibility is still not well understood. Several cases have been reported of patients with both MPN and multiple myeloma (MM). These authors tested whether MPN and MM have overlapping genetic susceptibility loci. They analyzed 23 known MM risk loci in participants from a case‐control study of MPN, including 460 cases and 880 controls. While no individual SNP reached statistical significance, a polygenic risk score showed an association with MPN risk, suggesting that several MM risk loci in combination could influence the risk of MPN.